Comparison of Outcome Between Early and Delayed Repair of Flexor Tendons - Naseem, Aiman; Ali, Faisal Akhlaq; Ali, Hyder; Waheed, Usamah bin; Ali, Mehak; Tasleem, Saima (Pakistan Armed Forces Medical Journal, 2024)
Objective: To determine the association of functional outcome for flexor tendon repair for the surgery timings.Study Design: Case Series.Place and Duration of Study: Plastic and Reconstructive Surgery Department, Dr Ruth KM Pfau Civil Hospital, Karachi Pakistan, from Apr to Sep 2021.Methodology: A total of 98 patients were equally divided into the early duration of tendon repair and the delayed duration of tendon repair. Patients were assessed to evaluate the functional outcome of flexor tendon repair in terms of tendon power assessed by the MRC scale, active movement at joints and the incidence of rupture. Functional outcome was assessed as Excellent (75-100), Good (50-74), Fair (24-49) and Poor (0-24).Results: In early repair, tendon power on the second post-operative day was observed as 11(22%) patients had movement against gravity but were powerless than normal, and 39(78%) patients had maximum strength. In comparison, in delayed repair, 5(10%) patients had movement against gravity but not against resistance, and 45(90%) patients had movement against gravity but were more powerless than normal. The active motion on the second post-operative day in early repair cases, 47(94%) patients had excellent active motion, while 30(60%) patients had good active motion in delayed repair. The tendon rupture was found 4(8%) in early repair and 10(20%) in delayed repair.Conclusion: Early tendon repair had excellent active motion and a lower ratio of tendon rupture than delayed repair.